Mesenchymal Stem Cell Exosomes as a New Strategy for the Treatment of Diabetes Complications - Xiong, Jiachao; Hu, Hao; Guo, Rong; Wang, Hui; Jiang, Hua (Frontiers in Endocrinology, 2021)
Diabetes mellitus (DM) has now developed into a worldwide metabolic disease, which is characterized by a relative or absolute lack of insulin secretion leading to chronically increased blood glucose levels. Diabetic patients are often accompanied by multiple macrovascular and microvascular complications such as diabetic kidney injury, diabetic encephalopathy and diabetic foot, which is an important killer that damages the quality of life and survival status of patients. Mesenchymal stem cell exosomes (MSC-Exos) possess repair functions similar to MSCs, and low immunogenicity, easy to store and transport. MSC-Exos have been proven to show excellent repair effects in repairing various organ damages. This article reviews the application of MSC-Exos in the treatment of DM and its common complications. MSC-Exos may become an effective treatment for DM and its common complications.